Evaluasi Dose Volume Histogram pada Perencanaan Simultaneous Integrated Boost IMRT Karsinoma Nasofaring Pediatrik: Laporan Kasus - Mariska Salsabila; Km Agus Bima Sakti; I Putu Andreana (KOLONI, 2026)
Pediatric nasopharyngeal carcinoma (NPC) is a rare case that requires special attention in radiotherapy planning due to the high risk of long-term side effects on developing tissues. Simultaneous Integrated Boost Intensity-Modulated Radiation Therapy (SIB-IMRT) enables simultaneous dose delivery to multiple target volumes according to clinical risk levels. This study aimed to evaluate dose distribution based on Dose Volume Histogram (DVH) parameters and Patient-Specific Quality Assurance (PSQA) results in SIB-IMRT planning for a pediatric NPC patient. This study was a case report using a descriptive dosimetric evaluation approach. Data were obtained from the Treatment Planning System, including DVH parameters for target volumes (PTV70, PTV60, and PTV54), organ at risk (OAR) dose parameters, and PSQA results using the Portal Dosimetry method. The evaluation showed that PTV70 fulfilled the dose coverage criteria based on ICRU Report 83, whereas PTV60 and PTV54 did not achieve optimal coverage, indicating a dosimetric compromise during treatment plan optimization. All OAR doses remained within tolerance limits according to the CORSAIR guideline. PSQA evaluation demonstrated a gamma passing rate of 99.8% using 3%/2 mm criteria with a 10% dose threshold. SIB-IMRT in this case demonstrated a balance between high-risk target prioritization, OAR protection, and dose delivery accuracy.